The Effect of Wet Therapy on Blood Pressure Reduction in Hypertension Patients in the Clinic Bekam Lahtahzaan Karanganyar - Windarti; Noor Sari Aditiya; Dwi Lestari Palupi (Proceeding of International Conference on Science, Health, And Technology, 2019)
Hypertension and its incidence rate in Indonesia become a phenomenon. Based on the report of the development of the health status of the Indonesian people to the national and provincial levels. The purpose of this study to determine the effect of cupping therapy on the decrease in blood pressure in patients with hypertension. This research uses Quasi experiment method to find out whether or not the result of "something" is imposed on the subject under study. Analysis of data in this study use paired t-test. The total population in this study were 30 respondents. Sampling in this research is as many as 30 respondents taken using total sampling technique. Based on the result of paired t-test, the significant value of p-value is 0.000 because (p <0,05) it can be concluded that there is influence of wet cupping therapy to decrease of blood pressure in hypertension patient. in hypertensive patients.